The The Vector Error Correction Model (VECM) in Analyzing the Impact of Economic Growth, Population Growth, and Carbon Emissions in Indonesia - Daffa Nanda Pratama; Neli Aida; Asih Murwiati (International Journal of Economics, Management and Accounting (IJEMA), 2025)
Managing carbon emissions is a pivotal challenge in Indonesia due to its significant impact on climate change and environmental sustainability. This study aims to examine the dynamic relationships between economic growth, primary energy consumption, and carbon emissions in Indonesia, employing the Vector Error Correction Model (VECM) approach. Using annual data from 1996 to 2023 sourced from the World Bank, the analysis investigates both short-term and long-term effects of the independent variables on carbon emissions. The findings reveal that primary energy consumption exerts a substantial and consistent impact on increasing carbon emissions across both time horizons, whereas the influence of economic growth appears more variable and less pronounced. The Impulse Response Function (IRF) analysis demonstrates a persistent upward trend in carbon emissions following shocks from primary energy consumption. Moreover, the Variance Decomposition analysis highlights that by the 25th period, primary energy consumption accounts for 23.79% of the variance in carbon emissions, whereas economic growth contributes only 4.09%. These results underscore the urgent need for Indonesia to prioritize energy transition policies that promote the adoption of renewable energy sources and improve energy efficiency. Such measures are essential to mitigate carbon emissions and support the country’s commitment to sustainable development and environmental preservation.